2002
DOI: 10.1177/101053950201400203
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Intelligent Laboratory Information System for a Community Health Promotion Centre

Abstract: This study aimed to develop an Intelligent Laboratory Information System (ILIS) for the community health promotion centre in Kwachun city to help process an increasing amount of laboratory test data in an efficient manner, and to support the clinical decision-making of public health doctors. A sample of 170 cases was used for validation of the system. Overall, the system correctly predicted 92.5% of the cases. This paper also analysed the economic feasibility of the ILIS based on the Information Economics appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Almost all studies found that the analytics could lead to monetary savings, yet only 2 papers included implementation costs of the analytics. 33 , 62 These costs could, for instance, consist of licensing costs and costs of implementing analytics within a hospital system. Authors often recommended to continue development and focus on improving the analytics.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all studies found that the analytics could lead to monetary savings, yet only 2 papers included implementation costs of the analytics. 33 , 62 These costs could, for instance, consist of licensing costs and costs of implementing analytics within a hospital system. Authors often recommended to continue development and focus on improving the analytics.…”
Section: Resultsmentioning
confidence: 99%
“…LIS helps screen more people by increasing the capacity of a health promotion center, and brings in more revenue to the center [21]. The LIS, combined with a Clinical Information System such as Computerized Physician Order Entry and Electronical Medical Record, can support improvements in health care services [22].…”
Section: Internal It/is Environment Analysismentioning
confidence: 99%